BURNOUT SYNDROME AND DEPRESSION AMONG HEALTHCARE PROFESSIONALS IN MAIDUGURI TERTIARY HOSPITALS - Pindar S.K; SAIDU SA; Wakil MA; Jidda MS; Morakinyo A O; Coker MA (Ntec Specialist, 2012)
Background: Working in the Healthcare sector entails intensive work both physically and psychologically and can exert intense psychological and physical pressures. The negative consequences of the stress associated with work in the health care sector pose serious problems not only to the caregivers but also to the quality of patient care. Defining the extent of this problem has value for the health worker and the patients overall well-being. Objective: Determine the prevalence of Burnout Syndrome and Depression among clinical staff and non-clinical staff in two tertiary hospitals in Maiduguri. Method: It is a comparative study to assess the prevalence of burnout syndrome and depression among clinical and non clinical staff in tertiary health institutions in Maiduguri. Data was collected using the Becks depression inventory and the Mashlach burnout inventory. Results: A total of 420 respondents were recruited for this study with both groups being matched for age and sex. A relatively high level of burnout was observed among the 2 clinical staffs compared to the non clinical (21.5% versus 12.5%; χ =5.31, DF=185 p=0.021). Depression was however, found to be insignificantly higher among the clinical staffs (Twenty 20 (10.7%) vs. 14 (7.6%); χ2=1.096, DF=1, p-value 0.295). There was a significant relatedness between having burnout and depression (χ2 =7.238, DF=1, p=0.007). Conclusion: Burnout syndrome and depression are common among clinical staffs and there is relationship between depression and burnout syndrome. The negative consequences of this combination which is work related can have impact on the outcome of patient management. Findings call for detection and prevention of burnout syndrome among healthcare professionals in order to protect their well-being and that of the healthcare industry